Analisis Efektivitas Pengelolaan Retribusi Pasar pada Dinas Perdagangan, Perindustrian, Koperasi dan UKM Aceh Barat - Bayu Pamungkas (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The purpose of this study is to determine the effectiveness of market retribution management in West Aceh Regency in 2019-2022. This type of research is a case study, data obtained by conducting interviews and documentation. The data analysis technique used is quantitative data analysis techniques. The results of the study also show that the effectiveness in 2019-2022 has been effective. This is indicated by the value of effectiveness which is greater than the value of 90 percent. In 2019, the effectiveness value is 68.6 percent. Then in 2020 the effectiveness value increased by 81.5 percent. In 2021 the effectiveness value will increase again, namely 90.5 percent. And in 2022 the effectiveness value of the six months running from January to June is 53 percent. Means showing the value of the better effectiveness. If the value of effectiveness is greater, the acceptance of market levies will be greater. The realization of market retribution receipts from 2019-2022 is increasing.